Coordination of Boron‐centered Lewis Acids by organo‐substituted Phosphanylboranes. Issue 21 (16th August 2017) - Marquardt, Christian; Kahoun, Tobias; Baumann, Josef; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract : The reactions of the monomeric phosphanylboranes Ph2 P–BH2 · NMe3 (1a ) and t BuHP–BH2 · NMe3 (1b ) with the main group Lewis acids BH3 and BBr3 yield the adducts H3 B· Ph2 P–BH2 · NMe3 (2a ) and H3 B· t BuHP–BH2 · NMe3 (2b ), Br3 B· Ph2 P–BH2 · NMe3 (3a ), and Br3 B· t BuHP–BH2 · NMe3 (3b ). All these compounds were completely characterized by single‐crystal X‐ray structure analysis, NMR and IR spectroscopy as well as mass spectrometry and DFT computations. The secondary and tertiary phosphines1a and1b behave as classical Lewis bases to coordinate B X 3 ( X = H, Br) as terminal groups. Abstract :